Association of Liposome-Encapsulated Trivalent Antimonial with Ascorbic Acid: An Effective and Safe Strategy in the Treatment of Experimental Visceral Leishmaniasis - Castro, Renata A. O. (Public Library of Science, 2014)
BACKGROUND: Visceral leishmaniasis (VL) is a chronic debilitating disease endemic in tropical and subtropical areas, caused by protozoan parasites of the genus Leishmania. Annually, it is estimated the occurrence of 0.2 to 0.4 million new cases of the disease worldwide. Considering the lack of an effective vaccine the afflicted population must rely on both, an accurate diagnosis and successful treatment to combat the disease. Here we propose to evaluate the efficacy of trivalent antimonial encapsulated in conventional liposomes, in association with ascorbic acid, by monitoring its toxicity and efficacy in BALB/c mice infected with Leishmania infantum. METHODOLOGY/PRINCIPAL FINDINGS: Infected mice were subjected to single-dose treatments consisting in the administration of either free or liposome-encapsulated trivalent antimony (SbIII), in association or not with ascorbic acid. Parasite burden was assessed in the liver, spleen and bone marrow using the serial limiting dilution technique. After treatment, tissue alterations were examined by histopathology of liver, heart and kidney and confirmed by serum levels of classic biomarkers. The phenotypic profile of splenocytes was also investigated by flow cytometry. Treatment with liposome-encapsulated SbIII significantly reduced the parasite burden in the liver, spleen and bone marrow. Co-administration of ascorbic acid, with either free SbIII or its liposomal form, did not interfere with its leishmanicidal activity and promoted reduced toxicity particularly to the kidney and liver tissues. CONCLUSIONS/SIGNIFICANCE: Among the evaluated posological regimens treatment of L. infantum-infected mice with liposomal SbIII, in association with ascorbic acid, represented the best alternative as judged by its high leishmanicidal activity and absence of detectable toxic effects. Of particular importance, reduction of parasite burden in the bone marrow attested to the ability of SbIII-carrying liposomes to efficiently reach this body compartment.